Effectiveness of Natural Traffic Noise Barrier: A Case Study at Muar Bypass (FT224) - Azahar, Aida Suryyanie; Abdullah, Mohd Ezree (Recent Trends in Civil Engineering and Built Environment, 2024)
Due to the increasing severity of noise pollution, a large number of road traffic noise models are now accessible around the world. This phenomenon necessitates the construction of road traffic noise barriers in such a manner that they effectively suppress noise behind them while simultaneously creating a low amount of reflected noise in the direction of the source. The purpose of this study was to investigate the effect of tree as a traffic noise barrier. The objective is also to measure the traffic noise and observe type of tree at Muar Bypass (FT224). A review as well as case studies were employed as research methodologies. The first approach used was a review study, in which the results of the previous study were compared to those of current study in order to determine whether there were any differences in outcomes in terms of various areas. When using the second method, a case study, the location chosen as the study area is Muar Bypass (FT224) in sections 4-5 since it meets all of the criteria necessary for this study. The distance between sources and receivers is 50 m. The findings revealed that the amount of traffic noise was reduced in the areas where the trees were denser. In addition, the researcher was able to identify nine different species of trees that occur in the region and have been identified as potential noise barriers in this study.